Peningkatan Pengetahuan Gizi Anak Sekolah melalui Media Interaktif E-Book di Era New Normal Covid-19 (Program Studi Gizi Jurusan Ilmu Kesehatan Masyarakat Fakultas Ilmu Keolahragaan Universitas Negeri Semarang (UNNES) bekerjasama dengan Persatuan Ahli Gizi (PERSAGI), 2022)
Nutritional problems that occur in school-age children are very short, very thin, and obese. The Covid-19 outbreak has resulted in monitoring nutrition and school health in Semarang unable to be carried out optimally. Such conditions further trigger the emergence of nutritional problems in elementary school children. This study aims to determine the effect of using interactive e-book media on the nutritional knowledge of school children in the new normal era of covid-19. This type of research is experimental with a one group pre-post test design. The sampling method used cluster sampling by randomly selecting one sub-district from 16 sub-districts in the city of Semarang. Gunungpati sub-district was chosen as the target of taking research subjects by selecting 20 students from the Nongkosawit State Elementary School 01 Semarang City as research subjects.The results showed that elementary school children were still found to be short, overweight, and obese. The Wilcoxon test showed that there was a significant difference in nutritional knowledge between before the use of the e-book compared to after its use (p<0.05), 3 subjects’ knowledge decreased, 1 remained, 16 increased.